2019
DOI: 10.1038/s41396-019-0491-z
|View full text |Cite
|
Sign up to set email alerts
|

Niche differentiation among annually recurrent coastal Marine Group II Euryarchaeota

Abstract: Since the discovery of archaeoplankton in 1992, the euryarchaeotal Marine Group II (MGII) remains uncultured and less understood than other planktonic archaea. We characterized the seasonal dynamics of MGII populations in the southern North Sea on a genomic and microscopic level over the course of four years. We recovered 34 metagenome-assembled genomes (MAGs) of MGIIa and MGIIb that corroborated proteorhodopsin-based photoheterotrophic lifestyles. However, MGIIa and MGIIb MAG genome sizes differed considerabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 74 publications
(155 reference statements)
3
63
4
Order By: Relevance
“…The relative abundance of differentially abundant MGIIa OTU001 in the PA fraction showed a strong negative correlation (R = − 0.7008) with the C: N ratio, suggesting their preference for fresh and highly liable organic matter. Metagenomic analyses of the MGII group showed the presence of protein (Iverson et al 2012 ; Orsi et al 2015 ; Orellana et al 2019 ; Rinke et al 2019 ), lipids, and carbohydrates degradation pathways (Orsi et al 2016 ; Xie et al 2018 ) indicating their role in the transformation of dissolved (Orsi et al 2016 ) as well as particulate (Orsi et al 2015 ) organic matter in the marine ecosystem. distLM and db-RDA analysis of the ASV-level data also showed that PON and C: N ratio were the most significant variables explaining the variation in FL and PA communities, respectively (Supplementary figure S.3), which is similar to our observations from the OTU-level data.…”
Section: Resultsmentioning
confidence: 99%
“…The relative abundance of differentially abundant MGIIa OTU001 in the PA fraction showed a strong negative correlation (R = − 0.7008) with the C: N ratio, suggesting their preference for fresh and highly liable organic matter. Metagenomic analyses of the MGII group showed the presence of protein (Iverson et al 2012 ; Orsi et al 2015 ; Orellana et al 2019 ; Rinke et al 2019 ), lipids, and carbohydrates degradation pathways (Orsi et al 2016 ; Xie et al 2018 ) indicating their role in the transformation of dissolved (Orsi et al 2016 ) as well as particulate (Orsi et al 2015 ) organic matter in the marine ecosystem. distLM and db-RDA analysis of the ASV-level data also showed that PON and C: N ratio were the most significant variables explaining the variation in FL and PA communities, respectively (Supplementary figure S.3), which is similar to our observations from the OTU-level data.…”
Section: Resultsmentioning
confidence: 99%
“…Thaumarchaeota MG I and Euryarchaeota MGIIb in the winter and Euryarchaeota MGIIa in the summer exist in various ecotypes in the coastal surface waters of the western Mediterranean Sea, characterized by different activity patterns (Hugoni et al 2013). Furthermore, several recent studies on the Euryarchaeota MGII group in coastal and open ocean systems identified diverse subclades with different ecological niches and lifestyles including members able to utilize taurine (Orellana et al 2019; Pereira et al 2019). Alteromonas phylo‐ and ecotypes also drastically differ in their utilization efficiencies of specific C‐compounds (Gómez‐Consarnau et al 2012; Sarmento and Gasol 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, intrapopulation microdiversity has also been proposed as a measure of evolutionary success. High diversity corresponds to populations with high temporal persistence and therefore greater adaptive success in their environment (17,27). In contrast, less diversity is associated with populations that have undergone a recent clonal sweep (18,27).…”
Section: Importancementioning
confidence: 99%